HEALTHCARE INBOX MANAGEMENT: AUTOMATING COMMUNICATION WORKFLOWS FOR CLINICAL EFFICIENCY - Saroj Kumar Rout, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article examines the transformation of healthcare communication through automated inbox management systems, focusing on their impact on clinical efficiency and patient care. The article examines core components, automated organizational features, workflow optimization, security measures, and implementation strategies in healthcare settings. The article analyzes how centralized communication hubs, message categorization systems, priority-based routing, and EHR integration work together to streamline healthcare communications. It explores the evolution of automated features including message classification, priority scoring, urgency detection, and smart filtering capabilities that enhance operational efficiency. The article also evaluates the implementation of advanced security protocols, compliance measures, and best practices in healthcare communication systems. Through detailed analysis of workflow optimization, team collaboration features, and performance monitoring, this article demonstrates how modern communication systems address traditional healthcare communication challenges while improving provider satisfaction and patient care quality. The findings highlight the significant role of automated inbox management in reducing provider burnout, enhancing patient response times, and maintaining secure, efficient healthcare operations.